ANALYZE ACUTE PARAPROCTITIS - A.U, Bobokulov; M.K, Usmonkulov; F.U, Babakulova; V.Y., Toxirova (Journal of Medical Genetics and Clinical Biology, 2024)
One of the most common diseases in emergency proctology is acute paraproctitis, the incidence of which, according to our data, occupies a leading position in the structure of proctological diseases. Acute paraproctitis is the most complex form of purulent inflammatory processes. According to the literature, patients with acute paraproctitis make up 0.5-4% of people with general surgical pathology and 20-40% of the structure of proctological diseases. The number of these patients and the increasing resistance of microbes require the development of more effective treatments.